King, Power, and Trading Ports: West Coast of Sulawesi in the Archipelago Spice Trade Route - Ahmadin (Jurnal Ilmu Sosial dan Humaniora, 2022)
South Sulawesi, which we find today as one of the provinces in Indonesia, is a peninsula that has an important role in the country's maritime history. On the west coast of Sulawesi, there are several kingdoms that have an important role in the archipelago's shipping and trade activities. This is due to its position on the Indonesian shipping route from west to east or vice versa. Thus, when discussing the strip and the spice trade as an important commodity of the world, then the gait of the kingdoms in this region becomes interesting to study. This paper discusses several kingdoms involved in spice trade activities, such as the Gowa Kingdom, the Tallo Kingdom, the Siang Kingdom, the Tanete Kingdom, the Suppa Kingdom, and also the Bantaeng Kingdom. Although only the Kingdoms of Gowa and Tallo are considered to be at the forefront of trade activities, but some kingdoms that have abundant produce also play a role as suppliers of various commodities that can be exchanged for spices